Photoshop CS : - Galer, Mark (Elsevier, 2005)
This approach is a brilliant idea that has been much tried in multimedia applications, but the difference here is that the book isn't second best. It is the key document and is beautifully illustrated and set out as a result...this makes it something of an inspiration as well as a work of instruction." - Stills Audio Motion "First impressions of Photoshop CS: Essential Skills are that it is an exceptionally well laid out, clear, clean, well designed book with a good selection of images and an altogether user-friendly look...I would highly recommend it as an introduction to the digital darkroom for photographic and photo-illustrative imaging